An Analysis of the Different Style between British and American Phonological System in the Sophomores' Speech Errors at Senior High School - Sumawar Pratiwi; Sima Latta; Gabryela Aritonang; Rahmawati Rahmawati; Irma Khoirot Daulay (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research aims to discover and analyze the problems of speech process between British and American phonological system faced by the students. It particularly examines the impact of language phonotactics on speech errors. Data were collected from random sample of sophomores in SMAN 1 Labuhan Deli using descriptive quantitative method. Data collection in techniques started from  recorded, rated, and analyzed. The researchers put the data analysis results grouped into two parts, the frist one is total production of speech errors, then the second id analysis of chosen words in British and American accent which systematically categorized based on IPA and other indicators. According to the results, students were fail to speech smoothly. The data of students’ speech errors showed that the highest and lowest percentage happened in correction (193 times (14%) and slip of tongue 110 times (8%), with the mode value 13%. While in phonological systems data samples, either British or American has ryhthm as the indicator with the lowest score. Based on the data, the researchers found the mode value is in score  4. It means that the speech errors indicator, correction, occured by the affect of different rhythm between British and American accent, but the mistake did not really disturb the meaning.